PROPRIEDADES ELETRÔNICAS E ESPECTROSCÓPICAS DE COMPLEXOS DE METAIS DO GRUPO 11 - GUILHERME DUARTE MOLTOCARO (2025)
The search for new bioactive materials, such as antibiotics and antiparasitic agents based on coordination chemistry, has attracted the interest of researchers worldwide. Complexes featuring structural motifs commonly found in allopathic drugs, such as triazoles—widely present in antifungal, antiviral, and anxiolytic agents—and pyrazolines, which appear in antifungals, antivirals, analgesics, and chemotherapeutics, can enhance therapeutic properties while reducing toxicity. This work results from a collaboration between experimental and theoretical researchers aiming to better understand the electronic and spectroscopic properties of new materials containing triazole and pyrazoline ligands coordinated to group 11 metals, namely copper, silver, and gold. Simulations were performed using Density Functional Theory (DFT), a widely established computational methodology derived from quantum mechanics but employing rigorous approximations, as the exact solution to the Schrödinger equation for interacting many-electron systems is impractical. We investigated the efficiency of DFT and Time-Dependent DFT (TD-DFT) in describing the molecular structures and electronic transitions of seven complex molecular systems. Calculations were carried out using the Orca 5 and, primarily, the Gaussian 16 software packages. Initially, several exchange-correlation functionals were evaluated for their efficiency. The most suitable functionals, considering computational limitations, were selected to replicate the methodology on other structures. The results demonstrated good agreement between experimental and theoretical data, particularly for closed-shell complexes without unpaired electrons, with errors consistent with those reported in the literature. Key electronic transitions and the involved frontier orbitals were identified, and the orbital density surfaces were calculated to visualize these transitions. The absence of imaginary vibrational frequencies ensured that the optimized geometries correspond to energy minima, and the simulated infrared spectra successfully reproduced the main vibrational modes, with values reasonably close to experimental observations.